The making of an archbishop: the journal of John Strain 1857–1859;–Journal of John Strain, 1857–1859 - Tierney, Darren (The Innes review, 2025)
John Menzies Strain (1810-1883), was a Catholic priest whose journal (edited here), from 1857 to 1859 provides a vivid account of clerical life in Victorian Scotland. Through daily entries, Strain's professional dedication, pastoral duties, and engagement with civic and educational improvement are disclosed. The diary is interpreted in the introduction through interdisciplinary lenses, including literary and gender analysis, to consider themes of masculinity, respectability, and the priest's role as a moral and social guide. Strain's journal is positioned within the broader context of nineteenth-century diary writing, affording insights into Scottish Catholic historiography and the lived experience of religious leadership. The value of such sources in enriching historical narratives is drawn out and further scholarly attention to similar clerical diaries is encouraged.